Perayaan Undhuh-Undhuh di GKJ Purwokerto sebagai Media Komunikasi Multikultural di Era Globalisasi dalam Membangun Kerukunan - Maria Puspita; S. Bekti Istyanto (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2020)
During the annual Pentecostal Celebration by GKJ Purwokerto (Javanese Christian Church of Purwokerto), an event called Undhuh-undhuh (direct translation, “Harvesting”) is held. It serves a gratitude manifestation to God for the harvests. This celebration involves not only members of the congregation, but also surrounding communities and other inter-faith associates. This study aimed to find and to analyze the contextualization attempts of the Undhuh-undhuh celebration as a multicultural communication medium in today's globalized era; purposefully to build national harmony. This study employs the descriptive-qualitative research method. Data was collected through observation (participatory approach), in-depth interviews, and document scrutiny. There are six informants, they are the chairman of the GKJ Purwokerto church council (elders), Chairman of the Youth Committee (of the church), Chairman of Young Gusdurian Banyumas, head of Sapto Darma, head of Kranji ward, and church elders of GKI (Indonesian Christian Church) Gatot Subroto. This study indicates that the wave of diversity is inevitable in religious life. The emerging role of the church to preserve the harmony in diverse community has become an important part. The Church of GKJ Purwokerto, through its Undhuh-undhuh celebration, is able to develop multicultural communication with diverse community; which prone to clash and becomes inharmonious.